اثر تطبيق المواصفة الدولية ISO18000 لنظام إدارة الصحة والسلامة المهنية في أداء المورد البشري دراسة حالة - مؤسسة باتيميتال عين الدفلى: The impact of the application of the international standard ISO18000 for the occupational health and safety management system on the performance of the human resource-A case study of Batimetal,AinDefla - قويدر الواحد عبد الله; شايب الدور سلمى (Journal of North African Economies, 2025)
This study aimed to identify the impact of the application of the international standard ISO 18000 on the performance of the human resource, by knowing the extent of the commitment of the higher management of the institution in the application of the requirements of this specification in the institution of BATIMETAL, where occupational safety and health in the industrial institution constitutes an integrated system for the prevention of injuries and diseases Work-related, as well as protecting and promoting the health of workers, which aims to improve working conditions and the environment and achieve continuous improvement. It was applied to the workers of the establishment, where 72 questionnaires were randomly distributed and 50 of them were retrieved, and to analyze the data we used the Statistical Package for Social Sciences (SPSS). Through this study, we reached the following result, which is the existence of a significant effect of the application of the international standard ISO 18000 (occupational health and safety policy, planning, application and operations, examination and corrective measures, management review, continuous improvement) in the performance of human resources at the significance level of 0.05. Keywords: health management; occupational safety; human resource performance; Batimetal Foundation; International Standard ISO 18000.